2021
DOI: 10.3390/ijms222111493
|View full text |Cite
|
Sign up to set email alerts
|

TaWAK2A-800, a Wall-Associated Kinase, Participates Positively in Resistance to Fusarium Head Blight and Sharp Eyespot in Wheat

Abstract: Fusarium head blight (FHB) and sharp eyespot are important diseases of the cereal plants, including bread wheat (Triticum aestivum) and barley. Both diseases are predominately caused by the pathogenic fungi, Fusarium graminearum and Rhizoctonia cerealis. The roles of the wheat-wall-associated kinases (WAKs) in defense against both F. graminearum and R. cerealis have remained largely unknown. This research reports the identification of TaWAK2A-800, a wheat WAK-coding gene located on chromosome 2A, and its funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
0
10
1
Order By: Relevance
“…For the genes that were not induced in this study, the possibility of their participation in FHB resistance cannot be eliminated. For example, TaWAK2A-800 reportedly participates positively in the resistance responses to FHB; however, it was significantly induced upon Fg inoculation in the FHB-resistant wheat cultivar, Sumai 3 [24] but not in this study. This difference may result from the expression analysis in different varieties or the conditions of Fg treatment.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…For the genes that were not induced in this study, the possibility of their participation in FHB resistance cannot be eliminated. For example, TaWAK2A-800 reportedly participates positively in the resistance responses to FHB; however, it was significantly induced upon Fg inoculation in the FHB-resistant wheat cultivar, Sumai 3 [24] but not in this study. This difference may result from the expression analysis in different varieties or the conditions of Fg treatment.…”
Section: Discussioncontrasting
confidence: 70%
“…According to previous research, pectin and chitin can trigger the expression of WAK genes. For example, TaWAK7D transcript levels were elevated after pectin and chitin treatments [20], TaWAK2A-800 was significantly induced by chitin treatment [24], and chitin triggered the expression of the rice OsWAK91/92/14 genes [14]. In this study, 19 of the 20 selected TaWAKs were elevated after exogenous pectin treatment, and 12 of the 20 TaWAKs were induced after exogenous chitin treatment, thus demonstrating that the TaWAK family may contribute to the pectinand chitin-induced defense pathway in wheat.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…To date, no completely resistant wheat germplasm to R. cerealis has been identified, and chemical control is still limited [ 9 ]. Various studies have shown that using important resistance-associated genes would generate wheat with better resistance to sharp eyespot [ 5 , 6 , 9 , 10 , 11 , 12 , 13 , 14 ]. Therefore, exploration of effective resistance genes is a viable strategy to breeding wheat with resistance to sharp eyespot.…”
Section: Introductionmentioning
confidence: 99%
“…The next two papers studied the wheat-wall-associated kinase and like kinase receptors involved in pathogen resistance. Guo et al [10] wrote about the roles of the wheat-wallassociated kinases (WAKs) in defense against both F. graminearum and R. cerealis, which have remained largely unknown. This research reported the identification of TaWAK2A-800, a wheat WAK-coding gene located on chromosome 2A, and its functional roles in wheat resistance responses to FHB and sharp eyespot.…”
mentioning
confidence: 99%